A generalized epilepsy network derived from brain abnormalities and deep brain stimulation - Ji, Gong-Jun; Fox, Michael D.; Morton-Dutton, Mae; Wang, Yingru; Sun, Jinmei; Hu, Panpan; Chen, Xingui; Jiang, Yubao; Zhu, Chunyan; Tian, Yanghua; Zhang, Zhiqiang; Akkad, Haya; et al. (Springer Science and Business Media LLC, 2025)
Idiopathic generalized epilepsy (IGE) is a brain network disease, but the location of this network and its relevance for treatment remain unclear. We combine the locations of brain abnormalities in IGE (131 coordinates from 21 studies) with the human connectome to identify an IGE network. We validate this network by showing alignment with structural brain abnormalities previously identified in IGE and brain areas activated by generalized epileptiform discharges in simultaneous electroencephalogram-functional magnetic resonance imaging. The topography of the IGE network aligns with brain networks involved in motor control and loss of consciousness consistent with generalized seizure semiology. To investigate therapeutic relevance, we analyze data from 21 patients with IGE treated with deep brain stimulation (DBS) for generalized seizures. Seizure frequency reduced a median 90% after DBS and stimulation sites intersect an IGE network peak in the centromedian nucleus of the thalamus. Together, this study helps unify prior findings in IGE and identify a brain network target that can be tested in clinical trials of brain stimulation to control generalized seizures.